Sosialisasi dan Edukasi Tanaman Berkhasiat Peningkat Imunitas pada Lingkungan Sekolah Menengah Kejuruan Telekomedika Bogor - Nhadira Nhestricia; Nina Herlina; Chyntia Wahyuningrum (Pelita: Jurnal Pengabdian kepada Masyarakat, 2022)
The COVID-19 pandemic has led to a severe global recession with differential impacts within and across countries. As of August 2020, Indonesia’s COVID-19 case-fatality rate is higher than the world average. Preventive measures for the spread of infection in the form of physical distancing implemented in all educational facilities force educators and students to develop online learning technology, according to the Circular Letter of the Minister of Education and Culture of the Republic of Indonesia Number 4 of 2020. Changes in learning patterns pose problems for the academic community, including in schools. Bogor Telecomedika Vocational High School. Difficulties arise not only because of the lack of skill of students and teachers in using technology, but also the increased workload due to the number of subjects and the workload that must be completed. Objective: As an Indonesian who lives in a country with abundant natural resources, the use of medicinal plants as an immune enhancer is an alternative to improve health. Methods: This activity was conducted at the Vocational School of Telekomedika in the form of a webinar with 129 participants. The theme of the webinar contains socialization and education about plants that are efficacious for enhancing immunity and making herbal medicine as one of the implementations of their use, as well as providing information about herbal product entrepreneurship. Results: This activity had a positive impact on 80.6% of participants in significantly increasing knowledge about nutritious plants and skills in processing natural ingredients into herbal medicine for body immunity.